تأثير مشعر كتلة الجسم الوالدي قبل الحمل على نتائج الحمل - حسن, لؤي (Latakia University Journal -Medical Sciences Series, 2018)
مقدمة: يؤثر مشعر كتلة الجسم (Body Mass index) (BMI) عند الحامل بشكلٍ كبيرٍ على محصول الحمل الوالدي و الوليدي . هدف البحث : دراسة تأثير BMI الوالدي ما قبل الحملي على النتائج السيئة للحمل ( للأم و الوليد) لدى عينة من السيدات الحوامل السوريات . المواد و الطرق : شملت هذه الدراسة المستقبلية 200 حامل بعمر حملي أقل من 12 أسبوع من المراجعات لقسم العيادات الخارجية أو المقبولات في قسم التوليد و أمراض النساء في مشفى تشرين الجامعي , اللاذقية , في الفترة الممتدة ما بين آب 2017 – آب 2018 . تمت متابعة الحوامل حتى نهاية الحمل لتحديد نتائج الحمل الوالدية و الوليدية . تمّ تصنيف المشاركات في البحث إلى 4 فئات حسب قيمة BMI: ناقص الوزن (BMI > 18.5 كغ/م2) طبيعي الوزن(BMI 18.5 – 24.9 كغ/م2 ) , زائد الوزن (BMI : 25- 29.9 كغ/م2 ) , و بدين(BMI < 30 كغ/م2) . تم استخدام الانحدار اللوجستي لضبط العوامل المتداخلة . جرى تقييم النتائج الحملية الوالدية و الوليدية باستخدام نسبة الأرجحية (OR) و بفواصل ثقة (CI) 95% . النتائج : كانت نسب توزع المرضى حسب قيمةBMI على الشكل التالي : ناقص الوزن (5%), طبيعي الوزن (63%), زائد الوزن (18%), و بدين (14%) . بالمقارنة مع الحوامل مع وزن طبيعي , فقد وجدنا ازدياداً لدى الحوامل زائدات الوزن و البدينات في خطر حدوث الاختلاطات الحملية التالية حيث تم التعبير عنها ]بنسبة الأرجحية (OR) و فاصل ثقة 95% [ على الترتيب : ما قبل الإرجاج [5.45 (1.6–18.5), 4.8 (1.5–15.4)] , السكري الحملي [6.6 (1.6–26.6),4.9 (1.2–19.4)] انبثاق الأغشية الباكر[4 (1–16.1) , 3.9 (1.06–14.3)] , الولادة القيصرية [2.7 (1.18–6.4), 2.28 (1.04–4.9) ] , النزف بعد الولادة [4.3 (1.2-15.4),4(1.2 – 13.2)] , وليد كبير بالنسبة لعمر الحمل [4(1.2 – 12.7), 3.5(1.9-10.2)] . كان صغر الوليد بالنسبة لعمر الحمل (17.5 CI95% : 2.9 - 103) , انفكاك المشيمة (7.6 CI95% : 1.2 – 48.1) , والولادة الباكرة (7.2 CI95% : 1.2 – 20.2) أكثر شيوعاً و بفارقٍ هامٍ لدى مجموعة الحوامل ناقصات الوزن . الخلاصة : يترافق ازدياد BMI الوالدي مع العديد من نتائج الحمل السيئة . يزيد نقص الوزن الوالدي من خطر كلٍّ من الحصول Introduction: Maternal body mass index (BMI) has an impact on maternal and fetal pregnancy outcome. Aim : To investigate the effect of pre-pregnancy BMI on adverse maternal and neonatal outcomes in a sample of Syrian pregnant women attending Tishreen University Hospital . Materials and Methods: This was a prospective study. Total of 200 pregnant women who were less than 12 weeks gestational age and receiving prenatal care at outpatient clinic or admitted to Department of Obstetrics and Gynecology Tishreen university Hospital , Lattakia ,Syria , from August 2017 to August 2018 were enrolled in the present study and monitored until delivery to establish maternal and neonatal outcome. The subjects were categorized into four groups by BMI : underweight (BMI < 18.5 kg/m2), normal (BMI 18.5–24.9 kg/m2), overweight (BMI 25–29.9 kg/m2) and obese (BMI ≥ 30 kg/m2). Logistic regression was used to adjust the potential confounder. Maternal and neonatal outcomes were evaluated with odds ratio and 95% confidence intervals. Results : 5% , 63% , 18%, and14 % of the subjects were underweight, normal BMI, overweight and obese, respectively. Compared with women of normal BMI, the risk of the following outcomes was significantly increased in overweight and obese women and expressed as [OR (95% confidence interval)] respectively: pre-eclampsia [4.8 (1.5–15.4), 5.45 (1.6–18.5)]; gestational diabetes [4.9 (1.2–19.4), 6.6 (1.6–26.6)]; premature rupture of the membranes(PROM) [3.9 (1.06–14.3), 4 (1–16.1)]; cesarean section [2.28 (1.04–4.9),2.7 (1.18–6.4)]; postpartum hemorrhage [4 (1.2–13.2), 4.3 (1.2– 15.4)]; large-for-gestational age [3.5 (1.9–10.2), 4(1.2–12.7)]. However, small for gestational age (17.5,2.9 –103) , abruption placentae (7.6 , 1.2 – 48.1) , and preterm delivery (7.2 , 1.2 – 20.2) were significantly more common in the underweight group. Conclusion :Increased maternal BMI is associated with many adverse pregnancy outcomes. Maternal underweight increases the risk of having small-for-gestational age baby, abruption placentae and preterm delivery .